APLIKASI ‘URF DALAM EKONOMI ISLAM - Wahyu Syarvina; Sudirman Suparmin; Tuti Anggraini (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2022)
Urf is a habit that has been practiced by society and is considered good, it can be in the form of words or actions that do not violate Islamic law. Many behaviors or habits in people's lives have become traditions in everyday life. The tradition can be in the form of words or actions of general application. This study used qualitative research methods. Qualitative method is a method with understanding and extracting meaning to what happens to various individuals or groups, originating from humanitarian or social problems. While the type of research used in this research is library research. Based on the results of the analysis, it was found that the application of 'urf in Islamic economics includes activities or buying and selling greetings, bay al wafa contracts, providing guarantees for the purchase of electronic goods, handovers in foreign exchange transactions (taqabuth).